Sams teach yourself C++ in 24 hours, starter kit - Liberty, Jesse; Horvath, David B. ([S.l.] : Sams Publishing, 1999)
This up-to-date guide to C++ programming is all you need to teach yourself the basics in 24 hours. Jesse Liberty's Sams Teach Yourself C++ in 24 Hours is a hand-on guide complete with examples of syntax and detailed analysis of code. By the end of the book, you will have learned the fundamentals of C++, including managing I/O loops and arrays, object-oriented programming, and creating C++ applications. A CD is included that provides you with all the source code needed to develop the samples in the book as well as the Cygnus Insight Debugger and the Dev-C++ IDE. Join over 250,000 readers who have learned C++ programming from Jesse Liberty!